Preparation, characterization of mixed-valence antimony-tin phosphomolybdic polyoxometalates and application in the cyclohexanone oxidation in the presence of hydrogen peroxide - Maiouf, Fatma-Zohra; Boumechhour, Abdenour; Benadji, Siham; Dermeche, Leila; Mazari, Tassadit; Lancelot, Christine; Rabia, Chérifa (Comptes Rendus. Chimie)
In this work, a series of polyoxometalates (POMs), as soluble salts of formula Sn1.5PMo12O40, SbPMo12O40 and $H_{3-x}Sn_{x1}Sb_{x2}PMo_{12} O_{40}$ ($x=2x_{1}+3x_{2}$ and $x_{1}$, $x_{2}=$ 0–0.75) were synthesized using the cationic exchange method under stoichiometric conditions. They were characterized and tested in the oxidation of cyclohexanone using hydrogen peroxide in the absence of organic solvent, co-catalyst phase transfer compounds or surfactants. UV–Visible and X-ray photoelectron spectroscopic analyses showed a partially reduced state of POM with coexistence of the couples Mo(VI)/Mo(V), Sb(V)/Sb(III) and Sn(IV)/Sn(II), without affecting their structure, results confirmed by FT-IR and Raman spectroscopies. The reversible cyclic voltammetry analysis evidenced the valence change of the Mo species, Mo(VI)/Mo(V). The POMs are found to be active in the cyclohexanone oxidation reaction and among them the most efficient is $H_{0.75}Sb_{0.75}PMo_{12}O_{40}$ with 49% of adipic acid yield.